2020
DOI: 10.1177/0093854820942561
|View full text |Cite
|
Sign up to set email alerts
|

The Gendered Nature of Criminogenic Thinking Patterns Among Justice-Involved Clients: A Pilot Study

Abstract: Because much of our understanding of criminogenic thinking (antisocial cognitions) has been based on male justice populations, questions remain about the applicability of this construct to justice-involved women. Based on an item-level analysis of 216 justice-involved clients, results of this pilot study suggest that criminogenic thinking in women is relevant, and both overlaps with and diverges from that of men. In fact, the predictive accuracy for rearrest attained with a gender-responsive model developed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…As they stated, “[c]riminal thinking is a dynamic cognitive process malleable through an intervention that, if accurately measured, could serve as a crucial component of an individual’s treatment plan” (Sease et al, 2022, p. 145). Second, at the statistical level, studies that focus on gender differences in patterns of criminal cognitions must pay attention to gender differences in response patterns and interpretation of concepts represented in the instruments employed to provide accurate findings (Hubbard & Matthews, 2008; Jones et al, 2021; Vaske et al, 2016; Walters, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As they stated, “[c]riminal thinking is a dynamic cognitive process malleable through an intervention that, if accurately measured, could serve as a crucial component of an individual’s treatment plan” (Sease et al, 2022, p. 145). Second, at the statistical level, studies that focus on gender differences in patterns of criminal cognitions must pay attention to gender differences in response patterns and interpretation of concepts represented in the instruments employed to provide accurate findings (Hubbard & Matthews, 2008; Jones et al, 2021; Vaske et al, 2016; Walters, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women are more likely than men to explain their behaviors within the context of dysfunctional interpersonal relationships. A recent pilot study with 216 admissions to a criminal justice day reporting center in Connecticut (Jones et al, 2021) that used the Criminogenic Thinking Profile (CTP, Mitchell & Tafrate, 2012) found no gender differences in criminal thinking patterns. However, the analysis indicated that male participants exhibited higher tendencies toward justification of criminogenic thinking patterns, while women manifested a greater propensity toward manipulative thinking (Jones et al, 2021).…”
Section: Criminal Thinking and Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…Poor-quality social support can be a powerful risk factor in JI women, positively associated with age of first arrest and offending severity (Staton-Tindall et al, 2007b), in which case women's internal strengths are crucial as buffers against recidivism potential. Similar variables, such as improving self-esteem (emotional appraisal of self-worth) and self-efficacy (practical appraisal of ability to complete tasks), as well as independence (avoiding reliance upon men), are also important promotive internal indicators of strength in at-risk women (Gannon et al, 2010;Hartman et al, 2009;Jones et al, 2021;Van Voorhis et al, 2010). Among protective internal strengths, sobriety is associated with desistance in JI women, especially those living in remote areas who remained in the community (n = 146) compared to those who returned to custody (n = 138; Staton et al, 2019).…”
Section: Gender-neutral and -Responsive Strengthsmentioning
confidence: 99%